2015
DOI: 10.18632/oncotarget.5565
|View full text |Cite
|
Sign up to set email alerts
|

Expression of prokineticin-receptor2(PK-R2) is a new prognostic factor in human colorectal cancer

Abstract: The increased invasiveness of colorectal cancer cells is important for progression and metastasis to the surrounding organs. According to recent molecular biological studies, signaling through transmembrane Prokineticin-Receptor2(PK-R2) is likely involved in the ability of tumor cell to invade. However, no studies have evaluated the relationship between PK-R2 expression, ability of cancer to invade/metastasize, and patient prognosis in cases of resected colorectal cancer. Accordingly, we have examined these fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Generally, the identification of patients who were at high risk of recurrence depended on pathological characteristics, such as the depth of invasion, nodal metastasis, stage group, and perforation or invasion of adjacent organs [ 7 ]. Nevertheless, the clinical outcomes are diverse among patients, including those with similar clinicopathological parameters and treatments, because CRC is a biologically heterogenous disease and causes dysfunction of multiple proteins that control cell proliferation and survival [ 8 10 ]. Patients who are at the same clinical stage of CRC might have distinct molecular drivers and different prognoses.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the identification of patients who were at high risk of recurrence depended on pathological characteristics, such as the depth of invasion, nodal metastasis, stage group, and perforation or invasion of adjacent organs [ 7 ]. Nevertheless, the clinical outcomes are diverse among patients, including those with similar clinicopathological parameters and treatments, because CRC is a biologically heterogenous disease and causes dysfunction of multiple proteins that control cell proliferation and survival [ 8 10 ]. Patients who are at the same clinical stage of CRC might have distinct molecular drivers and different prognoses.…”
Section: Introductionmentioning
confidence: 99%
“…The PROK1 protein was identi ed as a vascular endothelial growth factor. Increased PROK1 expression is associated with angiogenesis involving hematogenous metastasis [34,37]. Besides direct invasion and hematogenous spread, peritoneal carcinomatosis could be occurred by lymphatic dissemination, which supports the risk factor of N1-2 [54,56,57].…”
Section: Discussionmentioning
confidence: 84%
“…Reasons for exclusion were recorded. Finally, 25 studies [3,8,[15][16][17][18][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] were included in the nal analysis (Fig. 1).…”
Section: Search and Selection Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tabata et al [33] reported EG-VEGF as a factor to strengthen cell invasion ability in colon cancer cell lines, by acting on MMP-2, MMP-7, and MMP-9 via prokineticin receptor 2. Later, Goi and his team defined EG-VEGF and its corresponding receptor PROKR2 as prognostic markers in colorectal carcinoma [34, 35] suggesting a common pathway with VEGF sustained by their finding regarding the enhancement of antitumor effects when it was simultaneously targeting VEGF and EG-VEGF [36]. Fewer data were reported in normal tissues about EG-VEGF mechanism of action.…”
Section: The Mechanism Of Action Of Eg-vegf Moleculementioning
confidence: 99%